Field Evaluation of Interactions Between Insects and Erwinia amylovora in a New York Apple Orchard - Matthew Boucher; Rowan Collins; Kayli Harling; Gabrielle Brind’Amour; Stephen Hesler; Karen Wentworth; Kerik Cox; Greg Loeb (PhytoFrontiers, 2021)
The role of insects in dissemination of Erwinia amylovora has been studied for over 100 years. Pollinating bees do not feed on bacterial ooze but are suggested to transmit between flowers. It has been suggested that various hemipteran species walk on bacterial ooze and subsequently shed acquired bacteria into their own feeding wounds. Dipterans have been observed readily feeding on ooze, but their importance has been understudied. The goal of this study was to advance understanding of the ecology of insect-mediated transmission of E. amylovora through field collections and observations conducted in a research apple orchard with actively oozing fire blight symptoms. We found that field-collected pollinating bees did not test positive for the bacterium, suggesting that their role in blossom blight dissemination may be overstated. Flies were prominent flower visitors, underscoring the need for further research into their role in bloom time bacterial dissemination. Flies were observed feeding on ooze droplets in the late spring and early summer and the insects retained bacteria for at least 7 days. Flies shed transmissible amounts of E. amylovora for the duration of the experiment. The role of hemipterans was not clarified in this study but it is possible that their role is indirect through interactions with other insects. Collectively, this research outlines the ecological role of different insects in disease transmission and underscores the underappreciated potential importance of flies, providing a roadmap toward a better understanding of the complex dynamics at play.[Figure: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license.